1986
DOI: 10.1148/radiology.161.1.3763872
|View full text |Cite
|
Sign up to set email alerts
|

Venous thrombosis: clinical and experimental MR imaging.

Abstract: Five venous thrombi were induced in the external jugular veins of three laboratory dogs, and were repeatedly imaged over 3 weeks using a 0.35-T magnetic resonance (MR) imager. MR magnitude and phase images, T1 and T2 relaxation times, venography, and histologic sections of these thrombi were evaluated to determine the changes in appearance on MR images with time. Venous thrombi appeared hyperintense compared with muscle on both relatively T1- and T2-weighted spin-echo sequences regardless of the age of the clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(13 citation statements)
references
References 0 publications
2
9
1
1
Order By: Relevance
“…Diagnosis is based only rarely on CT alone, usually on angiography 1 -8 and more recently on MRI, which is now the study of choice if available. 9 Manifestations of SLE are similar in our patients and in the five cases reported previously. There is an increased tendency to arterial and venous thrombosis, especially when lupus anticoagulant is present.…”
Section: Discussionsupporting
confidence: 89%
“…Diagnosis is based only rarely on CT alone, usually on angiography 1 -8 and more recently on MRI, which is now the study of choice if available. 9 Manifestations of SLE are similar in our patients and in the five cases reported previously. There is an increased tendency to arterial and venous thrombosis, especially when lupus anticoagulant is present.…”
Section: Discussionsupporting
confidence: 89%
“…To our knowledge, venous thrombus models in previous in vivo studies have been induced with thrombin injection or electric stimulation [16][17][18] and have shown signal patterns that are different from our study. It is possible that the thrombi observed in those studies have mainly consisted of platelets and fibrins [22].…”
Section: Discussioncontrasting
confidence: 78%
“…Stasis seems to play the most important role in thrombus formation based on the physiological and anatomical venous character [15]. In vivo studies with animal models of venous thrombosis using MRI have already been reported [16][17][18]. In those studies, venous thrombi were induced by thrombin injection or by electric stimulation to the vessel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-enhanced two-dimensional (2D) time-of-flight (TOF) MRA has long been employed for assessment of the deep venous system [24,25,26]. The technique's limited clinical impact mainly reflects lengthy acquisition times in combination with the inability to reliably display superficial and small deep veins in the calf [27].…”
Section: Introductionmentioning
confidence: 99%